International academic cooperation: status report of Universiti Pertanian Malaysia - Abdul Rahman, Alang Perang Zainuddin; Mahfoz, Napsiah; Omar, Ishak (1990)
Universiti Pertanian Malaysia is committed to three major functions: teaching,research and extension. In the prusuance of excellence and relevance in its teaching, research and extension programmes, UPM vigorously professes and promotes colloboration with relevant institutions within and outside the country. The implementation of the inter-university cooperation are usually executed through bilateral arrangements, networking and the formation of a consortium of universities. Such colloborations are usually based upon mutual interests and benefits. UPM has, to date, established bilateral cooperation with both local and oversees institutions in the form of colloborative research, short visits and exchanges of academic staff development programmes. The academic linkages and joint programmes established with foreign universities and centres has enabled UPM to attract several regional and network in UPM as well as to fund research and consultancy projects. The paper concludes by drawing attention to the need to focus on the planning and establishment of a coherent system of inter-university cooperation in post-graduate education and research.